Is the Disease Burden from COPD in Norway Falling off? A Study of Time Trends in Three Different Data Sources - Melbye,Hasse; Helgeland,Jon; Karlstad,Øystein; Ariansen,Inger; Langhammer,Arnulf; Wisløff,Torbjørn; Nafstad,Per; Nystad,Wenche (International Journal of Chronic Obstructive Pulmonary Disease, 2020)
Hasse Melbye,1 Jon Helgeland,2 Øystein Karlstad,3 Inger Ariansen,3 Arnulf Langhammer,4 Torbjørn Wisløff,1 Per Nafstad,3 Wenche Nystad3 1General Practice Research Unit, Department of Community Medicine, UIT the Arctic University of Norway, Tromsø, Norway; 2Norwegian Institute of Public Health, Division of Health Services, Oslo, Norway; 3Norwegian Institute of Public Health, Department of Non-Communicable Diseases, Oslo, Norway; 4Department of Public Health and Nursing, Faculty of Medicine and Health Sciences, NTNU, Norwegian University of Science and Technology, Trondheim, NorwayCorrespondence: Hasse MelbyeGeneral Practice Research Unit, Department of Community Medicine, UIT the Arctic University of Norway, Tromsø 9037, NorwayTel +4795213200Email hasse.melbye@uit.noBackground: Less smoking should lead to fewer COPD cases. We aimed at estimating time trends in the prevalence and burden of COPD in Norway from 2001 to 2017.Methods: We used pre-bronchodilator spirometry and other health data from persons aged 40– 84 years in three surveys of the Tromsø Study, 2001– 2002, 2007– 2008 and 2015– 2016. We applied spirometry lower limits of normal (LLN) according to Global Lung Initiative 2012. Age-standardized prevalence was determined. We defined COPD as FEV1/FVC1 Results: In the Tromsø Study, the age-standardized prevalence of daily smoking dropped from 29.9% to 14.1% among women and from 31.4% to 12.8% among men (P< 0.0001). The age-standardized prevalence of COPD dropped from 7.6% to 5.6% among women (P=0.2) and from 7.3% to 5.6% among men (P=0.003) and of moderate to severe COPD from 5.2% to 2.7% among women (P=0.0003) and from 4.6% to 3.2% among men (P=0.0008). Among men, the yearly age-standardized prevalence of hospitalization due to COPD exacerbation decreased from 3.6 to 3.0 per 1000 inhabitants aged 40– 84 years (P<0.0001). Correspondingly, dispensing oral corticosteroids or/and antibiotics for COPD exacerbations dropped from 6.6 to 5.8 per 1000 (P<0.0001), while dispensing maintenance treatment ...